Lasting Power Of Attorney - Provision Contemplating Help To Die West And East (Indonesia) Perspective - Destra, Edwin; Firmansyah, Yohanes; Hendsun; Afladhanti, Putri Mahirah (Indonesian Scientific Publication, 2023)
The enactment of legislation governing decision-making for incapacitated individuals serves a crucial purpose, primarily enabling individuals to proactively plan for future incapacity by appointing trusted agents to make decisions on their behalf. In the context of England and Wales, adults can achieve this through the utilization of a lasting power of attorney, as stipulated in the Mental Capacity Act 2005 (sections 9-14). Specifically, a health and care lasting power of attorney grants authority to an appointed agent to make day-to-day care decisions in situations where the individual is unable to do so. It is imperative for district nurses to obtain the consent of the appointed attorney before administering treatment to the donor. Furthermore, a district nurse should conduct a comprehensive review of the actions taken by the donor's attorney, involving consultation with the donor, the general practitioner (GP), and the attorney. Should conflicts regarding care persist, legal intervention by the courts may be necessary. Notably, life-sustaining or necessary therapies would continue in such instances. It is essential to emphasize that lasting health and care powers of attorney are not subject to illegality, encompassing situations where the donor expresses wishes for euthanasia or assisted dying. District nurses are required to obtain a copy of the health and care enduring power of attorney, respecting the authority of the appointed attorney to make decisions in cases where the donor lacks capacity. In the Eastern context, considerations of human rights, religion, ethics, and law collectively categorize euthanasia as a criminal act. Conversely, while Indonesia lacks specific regulations addressing euthanasia, various legal sources indicate that both seeking and performing euthanasia are deemed criminal activities.